Men's depression and suicide literacy: a nationally representative Canadian survey. (1st November 2016) - Oliffe, John L.; Hannan-Leith, Madeline N.; Ogrodniczuk, John S.; Black, Nick; Mackenzie, Corey S.; Lohan, Maria; Creighton, Genevieve
Abstract: Background : Male suicide prevention strategies include diagnosis and effective management of men's depression. Fundamental to suicide prevention efforts is public awareness, which in turn, is influenced by literacy levels about men's depression and suicide. Aim : The aim of this study is to examine sex differences in mental health literacy with respect to men's depression and suicide among a cohort of Canadian respondents. Methods : About 901 English-speaking Canadian men and women completed online survey questionnaires to evaluate mental health literacy levels using 10-item D-Lit and 8-item LOSS questionnaires, which assess factual knowledge concerning men's depression and suicide. Statistical tests (Chi-square, z -test) were used to identify significant differences between sex sub-groups at 95% confidence. Results : Overall, respondents correctly identified 67% of questions measuring literacy levels about male depression. Respondents' male suicide literacy was significantly poorer at 53.7%. Misperceptions were especially evident in terms of differentiating men's depressive symptoms from other mental illnesses, estimating prevalence and identifying factors linked to male suicide. Significant sex differences highlighted that females had higher literacy levels than men in regard to male depression. Conclusions : Implementing gender sensitive and specific programs to target and advance literacy levels about men's depression may be key to ultimately reducing depression and suicide among men in Canada.